Penerapan Media Pembelajaran Berbasis Online untuk Meningkatkan Pemahaman dan Hasil Belajar Teknik Dasar Menggiring Bola - Kuswati, Rini (Jurnal Pendidikan Indonesia, 2022)
There is a problem with the lack of student learning outcomes in the ability to dribble which is the background in this study. An increase in understanding and the acquisition of final grades of student learning through the application of the use of online-based learning media is the goal of this CAR. The action research used in this study is in the form of PTK (CAR) with the aim of knowing the application of online-based learning media in learning on the ability to dribble the ball in an effort to improve understanding and learning outcomes of students of SMP Negeri 16 Singkawang in class 9A for the academic year 2021-2022 a total of 31 people. Data were collected and retrieved using the psychomotor, affective and cognitive test instruments listed in the lesson plans. Based on the studies studied, it was found that the average score of learning acquisition on the material of students’ dribbling skills using online media was higher with an average value of 85.61 when compared to the acquisition of learning outcomes at the beginning before the action was only 66.94 and in the implementation of the first cycle with an average 78.84. The final result of this study shows that the basic technique of dribbling a soccer game has increased learning outcomes with the application of online-based learning media. This is shown based on the study of completeness in the activities before the action was taken there were 7 students (22.58%), in the first cycle activities were 17 students or 54.84% then there was an increase in completeness in the second cycle from 31 students with a percentage of 100% . The indicators for achieving learning mastery reach 75% - 100%. The application model of online-based learning media (utilization of the Whatsapp/Facebook messenger/Google Classroom & Youtube application) in the subject of dribbling skills in the PJOK of soccer games can contribute to efforts to increase the ability and learn the existing abilities of students of SMP Negeri 16 Singkawang Class 9 A to improve the acquisition of learning materials for dribbling skills.